Cost-effectiveness analysis of camrelizumab plus chemotherapy as first-line treatment for advanced squamous NSCLC in China - Shao, Taihang; Ren, Yinan; Zhao, Mingye; Tang, Wenxi (Frontiers in Public Health, 2022)
Objective Results of CameL-sq has revealed the clinical benefits to patients with advanced squamous non-small-cell lung cancer (sq-NSCLC). This study aims to evaluate the cost-effectiveness of camrelizumab plus chemotherapy to treat sq-NSCLC from the perspective of the Chinese healthcare system. Methods We used a partitioned survival model with a lifetime horizon to evaluate the cost-effectiveness of camrelizumab plus chemotherapy vs. chemotherapy in treating sq-NSCLC. Baseline characteristics of patients and key clinical data were extracted from CameL-sq. Costs and utilities were collected from the open-access database and published literature. Costs, quality-adjusted life-years (QALYs), life-years gained, and incremental cost-effectiveness ratios (ICERs) were chosen as economic outcome indicators. We also performed a sensitivity analysis, subgroup analysis, and scenario analysis to verify the stability of the basic analysis results and explore the results under different scenarios. Results Combination therapy added 0.47 QALYS and 0.91 life-years with an incremental cost of $6,347.81 compared with chemotherapy, which had an ICER of $13,572 per QALY. The probabilistic sensitivity analysis indicated that camrelizumab plus chemotherapy had a 37.8% probability of cost-effectiveness at a willingness-to-pay threshold (WTP) of 1 time GDP per capital. When WTP was set as 3 times GDP per capital, combination therapy had significant cost-effectiveness. Deterministic sensitivity analysis showed that cost of the best supportive care was the factor with the greatest influence. The subgroup analysis found that combination therapy was associated with cost-effectiveness in several subgroups, namely, patients with disease stage IIIB/IIIC and with PD-L1 tumor proportion score ≤ 1%. Scenario analysis showed that ICER was positively correlated with the price of camrelizumab. Conclusion In this economic evaluation, camrelizumab plus chemotherapy was unlikely to be cost-effective compared with chemotherapy in the first line therapy of sq-NSCLC from a perspective of the Chinese healthcare system. Reducing the price of camrelizumab and tailoring treatments based on individual patient factors might improve the cost-effectiveness. Our findings may provide evidence for clinicians in making optimal decisions in general clinical practice.